The Analysis of Teacher’s Wait Time 1 in EFL Classroom at Junior High Schools in Padang - Hanifha Kemalasari; Yetti Zainil (Journal of English Language Teaching, 2021)
Abstract They are still teachers who do not know the effectiveness of wait-time 1 in EFL classes, especially at junior high school in Padang. The purpose of this study aims to observe how the teacher's wait-time 1 implementation in the classroom and also what are the teacher's obstacles in implementing wait-time 1 in the classroom using stimulated recall interview (SRI). The participants of this study were 18 teachers at junior high school in Padang. The findings show that the average wait-time for 1 teacher at junior high school in Padang is 3.49 seconds, besides that the study also found that the wait-time for 1 teacher with English questions is longer than Indonesian. The study also found that the obstacles to implementing wait-time 1 came from the teachers themselves. Key words: wait-time 1, obtacles, stimulated recall interview